(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The Inner Biographical Map (IBM) is a visual-narrative model designed to help individuals build and understand their identity through lived experiences. By utilizing symbolic maps with colors, shapes, and spatial sequencing, IBM facilitates recognition of emotional turning points and the reinterpretation of past events. The study explores IBM as a framework for identity transformation, promoting self-reflection, coherence, and psychological integration. Participants engaged in interviews and created their own maps, which were analyzed using Interpretative Phenomenological Analysis (IPA) to uncover themes and emotional trajectories. The findings highlight a four-stage identity shift—disruption, meaning-making, emotional release, and integration—demonstrating a transition towards psychological coherence. IBM serves as both a research tool and a transformative framework that enhances self-awareness and integration of identity.